Glucose deprivation enhances resistance to paclitaxel via ELAVL2/4-mediated modification of glycolysis in ovarian cancer cells. Issue 1 (January 2022) - Park, Ga Bin; Jeong, Jee-Yeong; Choi, Sangbong; Yoon, Yoo Sang; Kim, Daejin
Abstract : The dysregulation of glycolysis regardless of oxygen availability is one of the major characteristics of cancer cells. While the drug resistance of ovarian cancer cells has been extensively studied, the molecular mechanism of anticancer drug resistance under low-glucose conditions remains unknown. In this study, we investigated the pathway mediating drug resistance under low-glucose conditions by examining the relationship between embryonic lethal abnormal vision Drosophila homolog-like (ELAVL) protein and glycolysis-related enzymes. Ovarian cancer cells resistant to 2.5 nM paclitaxel were exposed to low-glucose media for 2 weeks, and the expression levels of ELAVL2, ELAVL4, glycolytic enzymes, and drug resistance-related proteins were elevated to levels comparable to those in cells resistant to 100 nM paclitaxel. Gene silencing of ELAVL2/4 using small interfering RNA prevented the upregulation of glycolysis-related enzymes, reduced lactate production, and sensitized 2.5 nM paclitaxel-resistant ovarian cancer cells to anticancer agents under hypoglycemic conditions. Furthermore, pharmacological inhibition of glycolytic enzymes with 2-deoxyglucose, a specific inhibitor of glycolysis, triggered caspase-dependent apoptosis, reduced lactate generation, and blocked the expression of drug resistance-related proteins under low-glucose conditions. These results suggest that the level of ELAVL2/4 is responsible for the development of chemoresistance through activation of the glycolysis pathway under glucose deprivation conditions.